WORKSHOP PENGGUNAAN APLIKASI POP DAN MENDELEY SEBAGAI PENUNJANG LITERATUR REVIEW PADA MAHASISWA - Muzammil, Ahmad Rabiul; Mariyadi, Mariyadi (Jurnal Abdi Insani, 2024)
Digital developments make it easy for students to organize and collect literature through the PoP and Mendeley applications. Therefore, this workshop aims to provide understanding and ability to workshop participants in operating PoP and Mendeley to help the literature review process. The workshop was held on September 25, 2023 which was attended by 26 students of Indonesian Language Education Study Program, FKIP, Untan. This workshop was carried out with the help of methods 1) lecture, 2) practice, and 3) question and answer. In this workshop, participants were guided to practice the application of PoP and Mendeley directly. The pretest results showed that the participants did not know the application of PoP and Mendeley as a reference organizer and reference collection tool. After the training, there was an increase in students' ability to input citations, bring up bibliographies, and change citation styles using the Mendeley application and succeeded in providing test participants with an understanding and ability to function PoP as a research metadata collection tool. The interest of the test participants was very high and the workshop has succeeded in giving confidence to the participants that the Mendeley and PoP applications will be useful for them in the future, especially in writing academic texts, which shows that this workshop has succeeded in increasing students' knowledge and ability to utilize PoP and Mendeley in the reference collection process.